A internacionalização da pós-graduação no âmbito de uma universidade pública federal e na perspectiva dos seus docentes pesquisadores - Méa, Liliane Gontan Timm Della (2017)
The Doctoral Thesis now presented was developed in the context of the research line “Formation, knowledge and professional development”, of the Post-Graduation Program in Education (PPGE). It is bind to the Research Group about Universities/GEU certified by the Federal University of Santa Maria (UFSM) and added to the GEU Network, coordinated by the Federal University of Rio Grande do SUL (UFRGS). It aimed to analyze the context of evaluation of the Post-Graduation Programs (PPG) of UFSM by the Higher Education Personnel Improvement Coordination (CAPES), in the perspective of internationalization and its implications in the institutional development and the teacher professional development. Articulates three reference points: National Evaluation System of Post-graduation, Internationalization and Teacher Professional Development. The context researched at UFSM is constituted by the Post-Graduation Programs evaluated by CAPES in the triennium 2010-2012 and in the quadrennium 2013-2016, with the concept 5 to 7, being subjects its teachers and mangers. It is a research in education, qualitative-quantitative, of the multiple case study type. The triangulation of information covers three sets of information: documental analyzes of the Brazilian educational politics, of the institutional regimentation and evaluative reports; online quiz sent to the totality of the teachers effectively registered at the institutional platform, identifying the establishment of demand and the internationalization processes and narrative interviews with managers of PPG, searching its perception of the internationalization, the institutional context and teacher professional development, being analyzed by Discursive Textual Analysis. The thesis sustains in its theoretical grounded argumentation and methodologic in the actual knowledge of the subject, listing in its final considerations, indicators and suggestions to the internationalization process demands as a PPG 5,6 and 7 differential, requiring the strategies improvement to the institutional development and the permanent professional development of its teaching researchers, listening its institutional politics needs to the internationalization and promotion to the research and its publishing in international publishers of high stratum and recognition by specifics areas of knowledge of each Post-Graduation Program of UFSM.